Mind versus body: Perceived stress and biological stress are independently related to cognitive decline - Kenny, Rose; Mc Crory, Cathal; O'Halloran, Aisling; Feeney, Joanne (My University, 2024)
Chronic stress may increase risk of age-related cognitive decline. ‘Stress’, however, is a multidimensional construct and few studies have investigated the inter-relationship of subjective stress and biological stress with cognitive decline. In this study, we examine the relationship between perceived stress and two measures of biological stress – allostatic load, indexing stress at the physiological level and leukocyte telomere length, indexing stress at the cellular level – with cognitive decline over a 12-year period in adults aged 50 and older. 3,458 participants (aged ≥ 50) from The Irish Longitudinal study on Ageing with measurements of allostatic load, telomere length and perceived stress at baseline and repeated measures of cognitive function were included. Hierarchical linear regression models with adjustment for multiple potential confounders were applied, and repeated stratified by sex in sensitivity analyses. Higher perceived stress at baseline was associated with lower cognitive function (β = 0.10, 95 % CI 0.12, 0.07, p <.001), with similar strength of associations across waves. There were significant interactions between measures of biological stress and wave; higher allostatic load was associated (X2 (18) = 64.4; p <.001), and telomere length was borderline (X2 (18) = 9.4; p =.09) associated with cognitive decline from 4-year follow-up onward. Sex stratified analyses revealed that the association between telomere length and cognitive decline was present in women only. Mutual adjustment did not attenuate associations in either case. The interactions between allostatic load and telomere length with perceived stress were not significant. Our findings suggest that subjective measures of stress and biological metrics may be independently related to cognitive function over time in older adults, hinting at the potential for different underlying mechanisms.
PUBLISHED
doi: https://doi.org/10.1016/j.bbi.2023.10.017
Keywords: Allostatic load; Telomere length; Perceived stress; Cognitive decline; Ageing